The Wiley-Blackwell Dictionary of Modern European History Since 1789 - Atkin, Nicholas James, 1960-; Biddiss, Michael D. (Michael Denis), 1942-; Tallett, Frank (Malden, MA : Wiley-Blackwell, 2011)
'The Wiley-Blackwell Dictionary of Modern European History Since 1789 is an authoritative and accessible reference guide to the major people, events, and issues that have shaped the development of Europe from the French Revolution to the present day. Features almost a thousand alphabetical entries on modern European history Offers extensive cross-references to enhance clarity and reveal historical links and connections, and a series of maps charting the evolution of modern European states Covers the whole of continental Europe, as well as relevant aspects of the British experience Written by a trio of distinguished historians of the period'--
'The Wiley-Blackwell Dictionary of Modern European History Since 1789 is an authoritative and highly accessible reference to the major people, events, and issues that have shaped Europe's development from the time of the French Revolution to the opening of the 21st century. This comprehensive guide features almost one thousand encyclopedic entries, written in collaboration by a trio of distinguished historians. The authors move well beyond basic definitions and descriptions to provide readers with a richer analytical understanding of the wider significance of historical events as they unfolded over the course of two centuries. Associated links and connections are revealed through an extensive series of cross-references. A sequence of maps charting the evolution of modern European states offers further clarity. The work covers the whole of continental Europe, as well as relevant aspects of the British experience. Lively and authoritative, The Wiley-Blackwell Dictionary of Modern European History Since 1789 is an indispensable reference guide to the broad sweep of historical events and experiences that have shaped the Europe we see today'--
Includes bibliographical references and index.
Keywords: History, Modern -- Encyclopedias; HISTORY / Modern / General; Europe -- History -- 1789-1900 -- Encyclopedias; Europe -- History -- 20th century -- Encyclopedias